Prognostic effect of body roundness index on all-cause mortality among US older adults - Yiling Yang; Xiaomin Shi; Xiaohong Wang; Shu Huang; Jia Xu; Chen Xin; Ziyan Li; Yizhou Wang; Yusong Ye; Sha Liu; Wei Zhang; Muhan Lv; et al. (Scientific Reports)
Abstract The Body Rounds Index (BRI) is an anthropometric indicator specifically developed to evaluate an individual’s obesity level, particularly emphasizing central or abdominal obesity. This study aimed to explore the relationship between BRI and all-cause mortality in older U.S. adults. The research sample comprised individuals aged 65 and older from the National Health and Nutrition Examination Survey (NHANES), eligible for mortality analyses between 1999 and 2018. We utilized Cox regression analyses, restricted cubic spline (RCS), threshold effects analysis, Kaplan–Meier curves, and subgroup analyses were conducted to assess how the BRI correlates with all-cause mortality among older adults in the U.S. To further ensure the robustness of our findings, we conducted sensitivity analyses. Among 5371 U.S. older adults (age ≥ 65), with an average age of 72.45 (standard deviation [SD]:5.65) years, 2884 (60%) were women. During the follow-up period, there were 2781 deaths from all causes among the 5371 participants. After adjusting for all covariates, a U-shaped association was identified between BRI and the all cause mortality. Compared to a BRI of less than 4.457, a BRI between 4.457 and 5.538 was associated with a 19% reduction in the likelihood of mortality from any cause (HR = 0.81, 95% CI = 0.69–0.95). A BRI between 5.538 and 6.888 was linked to a 8% reduction in mortality risk (HR = 0.92, 95% CI = 0.79–1.07), while a BRI exceeding 6.888 showed a 1% increase in this risk (HR = 1.01, 95% CI = 0.87–1.17). RCS analysis indicated a U-shaped relationship between BRI and all-cause mortality. The turning point was located at 4.546, with correlations observed both before and after this point. This NHANES-based study highlights the U-shaped relationship between BRI and all-cause mortality among U.S. older adults, suggesting that the BRI has predictive value for mortality outcomes. The findings offer compelling support for utilizing BRI as a non-invasive mortality risk screening tool.